2022
DOI: 10.1007/s10311-022-01498-7
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, transformation, bioaccumulation, risk and analysis of pharmaceutical and personal care products from wastewater: a review

Abstract: Almost all aspects of society from food security to disease control and prevention have benefited from pharmaceutical and personal care products, yet these products are a major source of contamination that ends up in wastewater and ecosystems. This issue has been sharply accentuated during the coronavirus disease pandemic 2019 (COVID-19) due to the higher use of disinfectants and other products. Here we review pharmaceutical and personal care products with focus on their occurrence in the environment, detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 211 publications
(293 reference statements)
0
23
0
Order By: Relevance
“…In turn, data on pharmaceuticals and their metabolites are comparatively scarce, even though they are some of the most important emerging pollutants, not only due to the growing use and diversity of compounds but also because their removal from wastewater tends to be inefficient [67]. Still, an interesting case is that of the 'conjugated oestrogen therapy' for menopause, a mixture of synthetic hormones that has been linked to breast cancer.…”
Section: Novel and 'Emerging' Pollutantsmentioning
confidence: 99%
“…In turn, data on pharmaceuticals and their metabolites are comparatively scarce, even though they are some of the most important emerging pollutants, not only due to the growing use and diversity of compounds but also because their removal from wastewater tends to be inefficient [67]. Still, an interesting case is that of the 'conjugated oestrogen therapy' for menopause, a mixture of synthetic hormones that has been linked to breast cancer.…”
Section: Novel and 'Emerging' Pollutantsmentioning
confidence: 99%
“…At the same time, it should be noted that the COVID-19 pandemic resulted in an increase in the consumption of certain drugs, including antibiotics, and thus an increase in their amounts in the sewage stream [ 123 ]. Due to the lack of drugs that were dedicated to the fight against the SARS-CoV-2 virus, drugs from various therapeutic groups were tested, i.e., antiviral drugs used in AIDS, antimalarial drugs (e.g., chloroquine and hydroxychloroquine), antibiotics (e.g., azithromycin), painkillers and combinations of these drugs (e.g., hydroxychloroquine and azithromycin) [ 124 ].…”
Section: Environmental Impacts Of Improper Disposal Of Unused/expired...mentioning
confidence: 99%
“…The data from 76 countries showed that the total global antibiotic consumption increased from 21.1 to 34.8 billion defined daily doses between 2000 and 2015 [2]. Studies have shown that antibiotics are detected in surface water [3,4], groundwater [5,6], domestic sewage [5,7,8], sediment [6,9,10], soil [11,12], and even drinking water [13,14] indicating that the environmental antibiotic pollution is widespread. In addition, the concentrations of antibiotics in Asian developing countries tend to be higher than those generally reported in European and North American countries [15].…”
Section: Introductionmentioning
confidence: 99%